SAT0122 Reduction of Peripheral Blood G-Ifn and IL-17 Producing T Cells After Therapy with Abatacept for Rheumatoid Arthritis. (23rd January 2014) - Scarsi, M.; Zanotti, C.; Chiarini, M.; Piantoni, S.; Imberti, L.; Frassi, M.; Bosio, C.; Rossi, D.; Paletti, A.; Tincani, A.; Airò, P.
Abstract : Background: Abatacept (ABA) is a fusion molecule used in the treatment of Rheumatoid Arthritis (RA), which is able to compete with the engagement of CD28, the receptor for most important costimulatory signal for T cells. CD28-mediated signaling regulate several T-cell functions, including inflammatory cytokine production and Treg differentiation. Objectives: The aim of our study was to evaluate the effect of therapy with ABA on peripheral blood T lymphocyte cytokine production and on the number of circulating Treg. Methods: In 24 RA patients treated with ABA for at least 6 months the proportion and absolute number of peripheral blood T cells producing γ-interferon (γ-IFN) and interleukin-17 (IL-17) after in vitro stimulation, as well as those of Treg were longitudinally evaluated by flow-cytometry at baseline and after 6 and 12 months. The EULAR response criteria were applied to evaluate the clinical response to treatment. Sixteen healthy donors (HD) of comparable age were used as controls. Results: At baseline, compared with HD, RA patients had a higher percentage of circulating Treg (median percentage of CD4+ T cells 6.4 (25 th -75 th percentile: 4.8-7.5) vs 4.7 (4.0-4.8); p: 0.041), as well as of CD4+ and CD8+ T-cells producing IL-17 (1.1% of CD4+ T cells (0.4-2.0) vs 0.5 (0.3-0.8); p: 0.021; 1.2% of CD8+ T cells (0.7-1.8) vs 0.7 (0.5-0.8); p:0.006). After 6 months of therapy with ABA, there was a decrease of the percentage of Treg (from 6.4% of CD4+ T cells (4.8-7.5) to 4.8 (3.0-6.3); p: 0.008), of γ-IFN- and IL-17- producing CD8+ T cells (from 25.6% (12.9-34.4) to 17.2 (11.9-28.7), p:0.033; and from 1.2% (0.7-1.8) to 1.0 (0.6-1.3), p:0.035, respectively), while that of IL-17-producing CD4+ T cells decreased at 12 months (from 1.1% of CD4+ T cells (0.4-2.0) to 0.3 (0.2-0.5); p:0.005). The number of Treg and of IL-17 producing T-cells that were higher than in HD at baseline normalized after ABA therapy. All these variations were statistically significant only in RA patients with good clinical response (n:17), whereas the variations were milder and not significant in the other group of patients (n:7). The reduction of IL-17 producing CD4+T cells absolute number was correlated with the reduction of disease activity, evaluated with the DAS28-CRP (r: 0.477; p: 0.039). Conclusions: These findings enhance our understanding of the mechanism of action of ABA underlying the relevance of the CD28-mediated signaling as pharmacological target for RA. Acknowledgements: We acknowledge Bristol-Myers-Squibb Italia for the support to our study Disclosure of Interest: None Declared